Analisis Komparatif Implementasi Metode Penyusutan Komersial Dan Fiscal Pada PT Semen Indonesia (Persero) Tbk - Salamatus Sa' diyah; Nur Hayati (VALUE, 2024)
This study aims to analyze the comparative implementation of depreciation methods according to commercial and fiscal in PT. Semen Indonesia (Persero) Tbk. Businesses can choose between three approaches outlined in commercial techniques, often known as SAK: the straight-line method, the sum of the years' digits method, and the double-declining balance method. Meanwhile, in the fiscal or taxation method there are two approaches: the straight-line technique and the double-declining balance method. Examining the commercial and fiscal approaches to fixed asset depreciation, this study aims to identify the most appropriate SAK depreciation technique for the company. The research findings show that the straight-line approach is superior to using other SAK depreciation methods, namely the double-declining balance method and the sum of the years' digits method. This is because it is more dominant and has a positive effect on the profitability of the company. In addition, when compared to the commercial depreciation approach, the depreciation value of fixed assets generated by the fiscal depreciation method is smaller. Because there are some fixed assets that cannot be depreciated such as buildings, roads, bridges and ports and also machinery because the useful life in the company is not in accordance with tax laws. Fiscal technique produces higher pre-tax profit on fiscal correction compared to commercial method. Because the depreciation figures of both methodologies are very different.